2019
DOI: 10.3329/uhj.v14i2.40283
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Outcome of Off Pump Coronary Artery Bypass Grafting in Patients with Low Ejection Fraction

Abstract: Coronary artery disease is increasing in developing countries. Revascularization surgery in such patients with amenable coronary anatomy is a valid option. Coronary artery bypass grafting in patients with low ejection fraction (EF <35%) is very challenging although it is performing successfully in department of Cardiac Surgery of Bangabandhu Sheikh Mujib Medical University now a days. The purpose of this study is to evaluate the safety and effectiveness of off pump coronary artery bypass grafting for EF e”3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…But another metaanalysis by Mariani et al (2013)43 , however, reported no significant benefit (OR 0.86; 95% CI, 0.71 to 1.04) with supplementing n-3 PUFA in preventing POAF. Additionally, the occurrence of POAF was similar to Sazzad et al (2018)44 and Salekin et al (2019) 45. Multicenter randomized control trials with a larger sample size among the Bangladeshi population undergone CABG can further generate knowledge regarding this issue that benefits the patient's outcome after cardiac surgery.…”
supporting
confidence: 71%
“…But another metaanalysis by Mariani et al (2013)43 , however, reported no significant benefit (OR 0.86; 95% CI, 0.71 to 1.04) with supplementing n-3 PUFA in preventing POAF. Additionally, the occurrence of POAF was similar to Sazzad et al (2018)44 and Salekin et al (2019) 45. Multicenter randomized control trials with a larger sample size among the Bangladeshi population undergone CABG can further generate knowledge regarding this issue that benefits the patient's outcome after cardiac surgery.…”
supporting
confidence: 71%
“…From our risk of bias assessment of the included studies, we determined that 2 randomized controlled trials were associated with high risk of performance bias due to the outcome assessors not being blinded to the type of intervention 12,. For the 14 prospective observational studies, 15,[18][19][20][21][22][23][24][25][26][27]30,31,35 there was high risk of bias in confounding factors. The non-ramdomized clinical trials 11,14,16,28,34 were also significantly biased due to absence of randomization.…”
Section: Quality Of Evidencementioning
confidence: 99%